Multiple [n]helicenes with various aromatic cores - Yin-Fu, Wu; Zhang, Ling; Zhang, Qianyan; Su-Yuan, Xie; Lan-Sun, Zheng (Organic chemistry frontiers an international journal of organic chemistry, 2022)
Multiple [n]helicenes are a type of distorted nanographene molecule characterized by the presence of more than one mono[n]helicene subunit (helically ortho-fused polyaromatic rings). An increasing number of studies on multiple [n]helicenes have been reported in recent years, mainly focusing on creating novel multiple [n]helicene structures and exploring new properties and applications. Usually, multiple [n]helicene molecules have a characteristic aromatic core, such as benzene, naphthalene, pyrene, perylene, hexabenzocoronene, corannulene, or azacorannulene. Due to the different cores, multiple [n]helicenes exhibit various topological structures and properties, revealing that the central core plays a significant role in multiple [n]helicenes. In this review, we summarize multiple [n]helicenes through a classification of cores, describe various synthetic strategies and methods to construct cores, and discuss the effect of the central core on the structural features, stereochemistry, photophysical properties, and potential applications. In the last section, we propose possible novel aromatic cores to create multiple [n]helicenes in the future.